2018
DOI: 10.3390/en11061596
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Carbon Storage and Its Contributing Factors—A Case Study in the Loess Plateau (China)

Abstract: Abstract:The Chinese Loess Plateau is an ecologically fragile and sensitive area. The carbon storage dynamics in this region and the contributions from land use/land cover change (LUCC) and carbon density from 2000 to 2010 were analyzed in this paper. Normalized difference vegetation index (NDVI), biomass and soil carbon data in 2000 were used for regression analysis of biomass and soil carbon, and an inversion analysis was used to estimate biomass and soil carbon in 2005 and 2010. Quadrat data, including abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Therefore, there would be some major components of trees that play a vital role in absorbing and storing carbon that are further explored in detail in the next section The biomass had a strong and significant positive linear relationship, which had the most notable influence on CS in this study. The findings of previous research verified that biomass was a major contributor to the carbon stock in trees [41,42]. Wellbrock et al [43] found 46 % of carbon storage in above and below biomass.…”
Section: Carbon Sequestration and Characteristics Of Treesmentioning
confidence: 67%
See 1 more Smart Citation
“…Therefore, there would be some major components of trees that play a vital role in absorbing and storing carbon that are further explored in detail in the next section The biomass had a strong and significant positive linear relationship, which had the most notable influence on CS in this study. The findings of previous research verified that biomass was a major contributor to the carbon stock in trees [41,42]. Wellbrock et al [43] found 46 % of carbon storage in above and below biomass.…”
Section: Carbon Sequestration and Characteristics Of Treesmentioning
confidence: 67%
“…The biomass had a strong and significant positive linear relationship, which had the most notable influence on CS in this study. The findings of previous research verified that biomass was a major contributor to the carbon stock in trees [41,42]. Wellbrock et al [43] found 46% of carbon storage in above and below biomass.…”
Section: Carbon Sequestration and Characteristics Of Treesmentioning
confidence: 67%
“…It also improved ecological quality and carbon sequestration capacity, as [47] reported. According to [48], it was confirmed that ~260 million tons of carbon were stored from 2000 to 2010, profiting from the gradual vegetation improvement in the Chinese Loess Plateau.…”
Section: Introductionmentioning
confidence: 99%